The Role of Social Capital in Preserving The Traditional Cuisine of Empal Gentong in Cirebon - Yunita; Ibnu Umar Fahdri; Dwiki Ilham; Ade Nur; Fani Septriani (ASANKA : Journal of Social Science and Education, 2025)
Preserving traditional culinary heritage is essential to maintaining local cultural identity amid modernization. This study analyzes the role of social capital in preserving Empal Gentong, a traditional Cirebonese dish with strong historical and cultural significance. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and document analysis. The results show that social capital—trust, social networks, and social norms—contributes significantly to preserving the authenticity of recipes, cooking techniques, and cultural values. Local culinary communities and intergenerational involvement play a key role in transmitting these values. Furthermore, collaboration between local governments, tourism stakeholders, and Micro, Small, and Medium Enterprises (MSMEs) is strengthened through social capital, enhancing promotion and preservation efforts. The study concludes that cultural culinary preservation relies on economic factors and strong social ties within the community. Strengthening social capital is therefore vital to sustaining local food heritage.